Pressure Ulcer Research Current and Future Perspectives - Bader, Dan L.; Bader, Dan L.; Bouten, Carlijn V.C.; Bouten, Carlijn V.C.; Colin, Denis.; Colin, Denis.; Oomens, Cees W.J.; Oomens, Cees W.J. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
This book provides an up-to-date scientific account of all aspects related to pressure ulcers and pressure ulcer research, as well as evidence-based knowledge of pressure ulcer aetiology. Further, it describes current and future tools for evaluating patients at risk. It comprises 20 chapters by renowned international experts in the field of pressure ulcer research. Among them are representatives of the European and American Pressure Ulcer Advisory Panels, basic researchers, clinicians and tissue viability nurses. Topics range from economic and legal aspects to evidence-based knowledge on prevention and treatment, aetiology, risk assessment and future aspects of pressure ulcer management. .